Pengaruh Pengangguran, Belanja Modal dan Belanja Bantuan Sosial terhadap Kemiskinan di Kota Banjarbaru Tahun 2010-2020 - Mellenia Medina, Salma; Nur, Muhammad Anshar (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This study was conducted to (1) analyze the effect of Unemlployment, Caapital Expeenditure and Social Assistance Expenditure simultaneously on Poverty in Banjarbaru City in 2010-2020; (2) analyze the effect of unemployment, capital expenditure and partial in Banjarbaru City in 2010-2020. Descriptive quantitative and using multiple linear regression analysis techniques with time series and using Eviews 10 software is a type of this research. This study provides results that show that independently, namely Unemployment, Capital Expenditure and Social Assistance Expenditure have a significant effect on Poverty in Banjarbaru City 2010-2020. Only the variable of Unemployment has a significant effect on Poverty in Banjarbaru City in 2010-2020.